Recent Advancements in the Field of Ni-Based Superalloys - Senthil Kumaran Selvaraj; G. Sundaramali; S. Jithin Dev; R. Srii Swathish; Rahul Karthikeyan; K. E. Vijay Vishaal; Velmurugan Paramasivam (Advances in Materials Science and Engineering)
In this review article, research papers related to recent developments in Ni-superalloy technologies have been reviewed in order to provide an insight into recent achievements and the potential for further study, research, and development in this field. In this paper, studies on various aspects of Ni-based superalloys are reviewed, such as production methods, which include widely used casting methods, as well as unconventional alternative procedures, novel techniques, or simulation and prediction of certain alloy casting properties. Reviewing was done by categorising the papers into 4 major categories: manufacturing of Ni-based superalloys, effects of alloying elements, physical and mechanical properties of Ni-based superalloys, and defects in Ni-based superalloys. The process used to make Ni-superalloy parts can have a huge impact on the production process efficiency, the final product’s quality and properties, and the defects formed in it. Investment casting is one of the most common methods for making Ni-superalloy parts. Manufacturing covers studies on various casting methods used to make Ni-based superalloy components, novel techniques and methods developed to improve casting procedures to produce better products, and alternative manufacturing methods like AM and HIP processing. Similar to production process, the role of alloying elements is also very important. Even minor changes in their compositions can cause significant changes in the final product. Simultaneously, these alloying elements appear to be more efficient in the development of new methods to control product quality, suppress defect formation, and improve material properties such as the creep and fatigue. As a result, the effects of various alloying elements used in castings of Ni-based superalloys are thoroughly examined. A material’s properties are its most important components. They assist the industrialist in selecting or developing a material based on the needs of the application/use. With this in mind, many researchers have conducted extensive research on physical and mechanical properties, as well as how to improve them. Fatigue life, stress rupture, creep properties, impact ductility, strain response, stress relaxation behaviour, and so on are some of the most important physical and mechanical properties of Ni-superalloys. This article thoroughly reviews various studies on these properties, how and by what factors they are affected, and how they can be improved. Another important factor to consider when making Ni-superalloy castings is defect formation, which can affect the properties of the final product. Freckle defects, hot tears, porosities, and slivers are some of the major defects that occur in Ni-superalloys during the casting process. This article also reviews in detail about these defects, how they form, and how they affect the final product. These defects were found to have a significant influence on a variety of properties, such as creep, fatigue behaviour, and fracture mechanism. Topics and areas such as reinforcement of Ni-superalloys with the help of CNCs and 3D printing of Ni-superalloys that can provide scope for potential future research are highlighted based on the above-reviewed papers.